Investigating the Impact of Cybersecurity Culture on Employees’ Cybersecurity Protection Behaviours: A Conceptual Paper - Lie, Laksana Budiwiyono; Utomo, Prio; Winarno, P.M. (ADI Publisher, 2021)
As technology and digital applications increase in volume and complexity, organization is facing greater security risks in cyberspace more than ever before. However, organizational cybersecurity requires more than just the latest technology. All the technology available to secure systems will not keep an organization secure if the people in the organization make bad or unexpected decisions that open up the system to attackers. To secure an organization, all employees of the organization must act positively to reduce company risks from cyberattacks. All leaders have a main responsibility to understand and align with the entire organization with cybersecurity objectives. Leaders need to keep continue to invest in security technologies and also need practical solutions for dealing with the human error of cybersecurity. The conceptual paper presented in this paper describes cybersecurity culture, external influencing factors, and organizational mechanisms, the elements that contribute to each employee of the organization that having protection behaviour from cyberattacks.